Usability Engineering and Evaluation of Usability In District Tourism And Culture Information Systems - Wasis Haryono (Data Science: Journal of Computing and Applied Informatics, 2019)
So far, the potential of natural resources has not been fully managed by the government or the community. For that we need a mature tourist object planning either by visitors or by developers. Communities need information provided on a mobile basis that can be accessed anywhere. This information is inseparable from the role of technology that supports so that applications can be used by tourists who want to visit either in the form of an address or location. Applications that are worthy of use are applications that have been tested usefulness or called usability. To test a system requires a questionnaire which one of them is SUMI (Software Usability Measurement Inventory). This study uses a method adopted from usability engineering lifecycle. The results of this study in the form of assessment with several criteria, so the application is feasible to use.